Management of children and adolescents with gray zone lymphoma: A case series. Issue 5 (9th February 2020) - Perwein, Thomas; Lackner, Herwig; Ebetsberger‐Dachs, Georg; Beham‐Schmid, Christine; Zach, Klara; Tamesberger, Melanie; Simonitsch‐Klupp, Ingrid; Lüftinger, Roswitha; Dworzak, Michael; Mann, Georg; Benesch, Martin; Attarbaschi, Andishe; et al.
Abstract: Background: Data on management of gray zone lymphoma (GZL) in children and adolescents are scarce. Procedure: This retrospective study assessed clinical characteristics and outcome in six Austrian patients with GZL less than 18 years of age (male‐to‐female ratio: 1:1; median age: 15.8 years). Results: Two patients each had a classical Hodgkin lymphoma (cHL)‐like and composite GZL subtype, and one patient each had a large B‐cell non‐Hodgkin lymphoma (LBCL)‐like and sequential GZL subtype. All had advanced disease with mediastinal and extranodal involvement. Five patients received an LBCL‐ and one patient a cHL‐directed polychemotherapy ± radiotherapy. Out of the former patients, three survived, including two who relapsed and underwent high‐dose chemotherapy with autologous stem cell rescue. The latter patient survived. Conclusions: GZL remains a diagnostic and therapeutic challenge, necessitating the development of novel treatment concepts performed in a prospective setting.